Prywatna apoteoza w Syrii okresu rzymskiego. Uwagi nad tondem brązowym znalezionym w Caesarei Paneas - Skupińska-Løvset, Ilona (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
This tondo was found in 1964 in a tomb in Caesarea Philippi (Caesarea Paneas), a foundation by Philippus, son of Herod the Great, on the site of Baalgad by the sources of the river Jordan. It is cast in thick bronze (0.5-1 cm thickness) and measures: Diam: 40 cm, H (of the bust): 34 cm, W (of the bust): 24 cm. It was fixed in a roughly lentoid shaped opening in the tondo, size 19 cm x 11 cm. The female represented in the tondo is young and carries a variant of the hairstyle often interpreted as proper to a goddess. She also wears a diadema. She has been interpreted either as a princess or as a goddess, probably Aphrodite. The present author considers the bronze as representing a young deceased female in the guise of a nymph. In literature such women who died young are often said to have been abduced by the nymphs. Found in a funerary context, the representation would be interpreted as a case of private apotheosis. There are several cases among the funerary portraits in Syria, suggesting deification post mortem. The type of representation belongs to the Greco-Roman repertory, but the tondo has both stylistic and technical features pointing to a local manufacture. A Trajanic-Hadrianic date is a possibility considering the chronology of this item.